Nanog maintains stemness of Lkb1‐deficient lung adenocarcinoma and prevents gastric differentiation. Issue 3 (13th January 2021) - Tong, Xinyuan; Chen, Yueqing; Zhu, Xinsheng; Ye, Yi; Xue, Yun; Wang, Rui; Gao, Yijun; Zhang, Wenjing; Gao, Weiqiang; Xiao, Lei; Chen, Haiquan; Zhang, Peng; et al.
Abstract: Growing evidence supports that LKB1 ‐deficient KRAS ‐driven lung tumors represent a unique therapeutic challenge, displaying strong cancer plasticity that promotes lineage conversion and drug resistance. Here we find that murine lung tumors from the Kras LSL‐G12D/+ ; Lkb1 flox/flox (KL) model show strong plasticity, which associates with up‐regulation of stem cell pluripotency genes such as Nanog . Deletion of Nanog in KL model initiates a gastric differentiation program and promotes mucinous lung tumor growth. We find that NANOG is not expressed at a meaningful level in human lung adenocarcinoma (ADC), as well as in human lung invasive mucinous adenocarcinoma (IMA). Gastric differentiation involves activation of Notch signaling, and perturbation of Notch pathway by the γ‐secretase inhibitor LY‐411575 remarkably impairs mucinous tumor formation. In contrast to non‐mucinous tumors, mucinous tumors are resistant to phenformin treatment. Such therapeutic resistance could be overcome through combined treatments with LY‐411575 and phenformin. Overall, we uncover a previously unappreciated plasticity of LKB1 ‐deficient tumors and identify the Nanog‐Notch axis in regulating gastric differentiation, which holds important therapeutic implication for the treatment of mucinous lung cancer. Synopsis: This study reveals the plasticity of LKB1‐deficient tumors, and identifies the Nanog‐Notch axis in regulating gastric differentiation. Combinational treatment of γ‐secretase inhibitor LY‐411575 and phenformin effectively blocked invasive mucinous adenocarcinoma IMA formation. Invasive mucinous adenocarcinoma (IMA) was promoted by Nanog deficiency in the KrasLSL‐G12D/+; Lkb1flox/flox KL mouse model. Concurrent loss of NANOG and LKB1 was frequent in human lung IMA. Mucinous differentiation was inhibited by perturbation of the Notch pathway. IMA was insensitive to phenformin treatment. IMA formation was blocked by a combinational treatment of LY‐411575 and phenformin. Abstract : This study reveals the plasticity of LKB1‐deficient tumors, and identifies the Nanog‐Notch axis in regulating gastric differentiation. Combinational treatment of γ‐secretase inhibitor LY‐411575 and phenformin effectively blocked invasive mucinous adenocarcinoma IMA formation.